2012
DOI: 10.1021/es300739r
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impacts of Biodiesel and Second Generation Biofuels on NOx Emissions for CARB Diesel Fuels

Abstract: The impact of biodiesel and second generation biofuels on nitrogen oxides (NO(x)) emissions from heavy-duty engines was investigated using a California Air Resources Board (CARB) certified diesel fuel. Two heavy-duty engines, a 2006 engine with no exhaust aftertreatment, and a 2007 engine with a diesel particle filter (DPF), were tested on an engine dynamometer over four different test cycles. Emissions from soy- and animal-based biodiesels, a hydrotreated renewable diesel, and a gas to liquid (GTL) fuel were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 61 publications
8
47
0
Order By: Relevance
“…For example, Soy B50 and An B50 show NO x increases of approximately 10% and 5%, respectively, for the UDDS cycle. This increasing effect of biodiesels on NO x emissions is consistent with previous studies (Karavalakis et al, 2009;Cheung et al, 2009;Hajbabaei et al, 2012). The degree of unsaturation and Cetane number of biodiesel are reported to be associated with NO x emissions (Knothe, 2005;Pham et al, 2013).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…For example, Soy B50 and An B50 show NO x increases of approximately 10% and 5%, respectively, for the UDDS cycle. This increasing effect of biodiesels on NO x emissions is consistent with previous studies (Karavalakis et al, 2009;Cheung et al, 2009;Hajbabaei et al, 2012). The degree of unsaturation and Cetane number of biodiesel are reported to be associated with NO x emissions (Knothe, 2005;Pham et al, 2013).…”
Section: Resultssupporting
confidence: 91%
“…A number of studies have suggested that biodiesel can lead to higher NO x emissions (Karavalakis et al, 2009;Cheung et al, 2009;Durbin et al, 2011;Hajbabaei et al, 2012). The potential for increase in NO x emissions has been recognized as a major concern to the application of biodiesel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of direct comparison of the effects of FAME biodiesels, HVORD and petroleum diesel on emissions from turbocharged, electronically controlled engines are available from the literature (Hajbabaei et al, 2012; Westphal et al, 2013; Kim et al, 2014), but the equivalent information for mechanically controlled, naturally aspirated engines is not readily available. This information is critical to underground mining operators that still have large fleets of light- and medium-duty vehicles powered by those engines.…”
Section: Introductionmentioning
confidence: 99%